(untitled) (Research, Society and Development, 2022)
Introduction: The chromosomal region 15q11-13 contains a group of genes essential for normal neurodevelopment and alterations in this region result in different syndromes. Among the most frequent alterations, there are chromosomal deletions and duplications. Duplications of chromosome region 15q11q13 occur as a supernumerary chromosome 15, and may occur as interstitial duplications. The main clinical manifestations are intellectual impairment, problems with vision, hearing, teething and in bones and joints. Currently, there are few cases reported in the literature about this genetic condition, which justifies the relevance of this study. Objective: To report a case of duplication in the chromosomal region 15q11q13 and describe the clinical manifestations. Methodology: This is a case report of a qualitative nature. Case report: J.V.A.S., male, eight years old, attended at the Associação de Pais e Amigos dos Excepcionais (APAE), in Anápolis, Goiás, Brazil, in 2017, diagnosed with neuropsychomotor developmental delay (ADNPM) and macrocrania. No complications during childbirth. The patient had head support at six months, sat up at nine months, walked and talked at one year and ten months. He attends school and has good interaction, but has learning difficulties. In 2018, the CGH – ARRAY (aCGH) revealed the presence of a duplication in 15q11.2q13.1 of approximately 6.1Mb classified as pathogenic. Results and discussion: Due to the rarity of this syndrome, we did not find a satisfactory number of articles that specifically addressed this duplication. Conclusion: It is necessary to carry out more studies, in the long term and through satisfactory samples, in order to elucidate the main aspects involved in this pathology.